Soil carbon, nitrogen, and phosphorus stoichiometry and its influencing factors in Chinese fir plantations across subtropical China - Tong, Ran; Wu, Tonggui; Jiang, Bo; Wang, Zhigao; Xie, Binglou; Zhou, Benzhi (Frontiers in Forests and Global Change, 2023)
The crucial roles of soil carbon (C) and nutrients and their stoichiometric characteristics in indicating the soil interior nutrient cycling and plant nutrient supply of forest ecosystems have been widely verified, whereas it has been less explored when considering the influencing factors regionally, especially for the widely cultivated plantation tree species. In the current study, the patterns of soil organic C (SOC), total nitrogen (TN), and total phosphorus (TP) stoichiometry in Chinese fir [Cunninghamia lanceolata (Lamb.) Hook] plantations across subtropical China were analyzed, and their influencing factors were also investigated. The results showed that the range of SOC: TN (C:N), SOC: TP (C:P), and TN: TP (N:P) ratios were 7.32–18.27, 20.15–230.48, and 2.11–15.05 with a mean value of 13.22, 83.50, and 6.05, respectively. Well-constrained correlations were found in SOC and TN, as well as in TN and TP. Soil TN and TP contents increased with increasing altitude, whereas soil C:N, C:P, and N:P ratios decreased. Soil TP content decreased, and the C:P ratio increased with increasing mean annual temperature (MAT) and annual total solar radiation (ATSR). Soil C:N, C:P, and N:P ratios increased with increased mean annual precipitation (MAP) and mean annual evaporation (MAE). Overall, our findings suggested that the soil nutrient supply is relatively adequate in Chinese fir plantations across subtropical China. Meanwhile, soil C, N, and P stoichiometric characteristics were affected by geographical and climatic variables to different degrees.